COMPARISON OF FLAT AND INCARCERATING SURFACE SOLAR SUPPORTED DRYING SYSTEMS FOR APRICOT DRYING - Mustafa Bahadır OZDEMIR; Mehmet Mustafa YATARKALKMAZ (Gazi Üniversitesi Fen Bilimleri Dergisi, 2018)
In this study, drying systems with flat and incarcerating surface absorbent plates were designed and manufactured for drying apricots, then their performances were compared. Experiments were carried out with slices 4-5 mm thick, with 76% moisture on wet basis. The measurements were made at 30 minute intervals in the experiments and the experiment was terminated when the difference between the following measurements was less than 1%. The drying process was carried out at 2,5, 3,0 and 3,5 m/s drying air velocities. As a result of the experiments, while the average temperature of the drying chamber of the flat surface drying system was found to be 45,96 ° C, the drying chamber average temperature of the incarcerating surface was found to be 49,04 ° C. In the flat surface drying system, the drying time lasts 390 minutes at all speeds, while the drying time of incarcerating surface drying system is 330 minutes at 3,2 and 3,0 m/s and 300 minutes at 3,5 m/s. It has been concluded that the incarcerating surface drying system performs drying at a speed of 2,5 and 3,0 m/s for 60 minutes and 3,5 m/s for 90 minutes shorter than the flat surface drying system.